Success in Academic Surgery - Chen, Herbert; Kao, Lillian S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This second edition book gives an overview of the other titles of the Success in Academic Surgery Series, and includes additional chapters on global surgery, surgical quality improvement and getting started in leadership. The Association for Academic Surgery (AAS) has been teaching how to become a successful academic surgeon to medical students, residents, and young faculty for over 20 years. Success in Academic Surgery, Second Edition reinforces the curriculum of the AAS courses and also provides guidance to individual surgeons who have not had the opportunity to attend these courses. This book is a valuable reference for medical students, surgical residents, and young surgical faculty.
Why Be an Academic Surgeon? Impetus and Options for the Emerging Surgeon-Scientist -- Timeline for Promotion/Overview of an Academic Career -- Reviewing the Literature/Developing a Hypothesis, Study Design -- Ethics in Surgical Research -- Analyzing Your Data -- Animal Models for Surgical Research -- Health Services Research -- Surgical Educational Research: Getting Started -- Translational Research and New Approaches: Genomics, Proteomics, and Metabolomics -- How to Write and Revise a Manuscript for Peer Review Publication -- Choosing, and Being, a Good Mentor -- Writing a Grant/Obtaining Funding -- Setting Up a (3z(BLab(3y (B(Clinical or Basic Science Research Program) and Managing a Research Team -- Work-Life Balance and Burnout -- Time Management.s
Keywords: Medicine; Surgery; Medicine & Public Health; General Surgery